The Risk Factors of Motorcycle Riders Traffic Accidents in Semarang City 2017 - Mochammad Malik Ibrahim; Mateus Sakundarno Adi; Suhartono Suhartono (Universitas Islam Bandung, 2020)
The incidence rate of motorcycle accidents in Semarang city increased every year in the period 2014–2016. The research related to the risk factor of traffic accident incidents on motorcycle riders in Semarang city is still scarce. This study aims to analyze the risk factors of traffic accidents on motorcycle riders in Semarang city. The type of research is an analytic observational study with a case-control design. The number of samples was 50 cases and 50 controls. The case is a motorcycle rider who had a traffic accident in Semarang city from July to November 2017. Control is a motorcycle rider who did not have a traffic accident. Data was analyzed bivariate and multivariate using logistic regression test backward LR method. Factors proven to be a risk factor for traffic accidents on motorcyclists are less alert (p=0.005, OR=4.255, 95% CI=1.540–11.759), non-distance habits (p=0.001, OR=5.209, 95% CI=1.997–13.584), and hasty behavior (p=0.029, OR=2.950, 95% CI=1.116–7.800). Conclusions, alertness, not keeping distance, and impulsive behavior are risk factors for traffic accident incidents on Semarang city motorcyclists. FAKTOR RISIKO KECELAKAAN LALU LINTAS PENGENDARA SEPEDA MOTOR DI KOTA SEMARANG TAHUN 2017Angka insidensi kecelakaan sepeda motor di Kota Semarang meningkat setiap tahun dalam kurun waktu 2014–2016. Penelitian terkait faktor risiko kejadian kecelakaan lalu lintas pada pengendara sepeda motor di Kota Semarang masih sangat jarang dilakukan. Penelitian ini bertujuan menganalisis faktor risiko kejadian kecelakaan lalu lintas pada pengendara sepeda motor di Kota Semarang. Jenis penelitian adalah studi observasional analitik dengan desain case control. Jumlah sampel 50 kasus dan 50 kontrol. Kasus adalah pengendara sepeda motor yang mengalami kecelakaan lalu lintas di Kota Semarang terhitung dari Juli hingga November 2017. Kontrol adalah pengendara sepeda motor yang tidak mengalami kecelakaan lalu lintas. Data dianalisis secara bivariat dan multivariat menggunakan uji logistic regression metode backward LR. Faktor yang terbukti sebagai faktor risiko kejadian kecelakaan lalu lintas pada pengendara sepeda motor adalah kurang waspada (p=0,005; OR=4,255; IK 95%=1,540–11,759), kebiasaan tidak menjaga jarak (p=0,001; OR=5,209; IK 95%=1,997–13,584), dan perilaku terburu-buru (p=0,029; OR=2,950; IK 95%=1,116–7,800). Simpulan, kurang waspada, kebiasaan tidak menjaga jarak, dan perilaku terburu-buru merupakan faktor risiko kejadian kecelakaan lalu lintas pada pengendara sepeda motor di Kota Semarang.